Theatrical research of laboratory discourse: Concepts, history of ideas, Russian context - Yu. G. Liderman (Шаги, 2022)
The article discusses laboratory discourse on the basis of Zara Abdullaeva's interviews with the theatre director and theorist Anatoly Vasiliev. Discourse analysis is becoming a method of analysis in theatrical studies. In particular, it is proposed to see the premises of a theatrical laboratory in production aesthetics. The article outlines the connection between laboratory theaters and productivist art and productivism (Boris Arvatov, Walter Benjamin). Thanks to the institutional criticism of the laboratory by Bruno Latour, the question is raised about the possibilities of mutual influence of laboratory theaters and society. Laboratory theater is considered in the article as a paratype of participatory art (Claire Bishop). The article provides information about the history of and research into laboratory theater in Russia. The method of discourse analysis is used in the article in relation to the recorded interviews of Anatoly Vasiliev and the interviewer Zara Abdullaeva. The mechanisms of the laboratory's influence on society identified by Bruno Latour allow us to take a fresh look at the various laboratory activities of Anatoly Vasiliev and at the comments and clarifications that he makes after the fact in relation to them.